Desenvolvimento e caracterização de bebida vegetal à base de amêndoa de castanha de caju, adicionada de achocolatado, leite de coco ou banana - Mesquita, Samara Alves de (2017)
Vegetable beverages are a segment of the market that has grown year after year. There are several raw materials used in the manufacture of such beverages. The use of cashew nut as raw material appears as an opportunity to obtain a healthy and lactose-free product, besides adding value to a raw material of high commercialization and easy to obtain in Ceará. Thus, the purpose of the present study was develop a vegetable beverage using cashew nut as raw material with added chocolate, coconut milk or banana; seeking to meet the consumers' wishes regarding their sensorial aspects and nutritional value, emphasizing the bioaccessibility of the minerals calcium and phosphorus. Considering the absence of studies on the sensorial aspects of the product, tests were carried out for its development (ideal scale and ordering preference) and acceptability (hedonic scale, check-all-that-aplly and purchase intention). In addition, physical-chemical parameters of the samples (pH, total acidity titrable by citric acid, total solids, centesimal composition, carbohydrate and energetic value) and color analysis were analyzed. The formulations were also subjected to an in vitro gastrointestinal digestion process in which they were evaluated according to the calcium and phosphorus minerals content before and after this digestion. Sensory tests proved that the addition of 3% sugar made the product acceptable, which was ratified from the high acceptance in the intention to purchase test. In the hedonic scale test, all samples obtained overall impression results within the acceptance area of the product. A correlation was made between the hedonic scale and Check-all-that-aplly in order to trace the sensorial profile of the products, and a sensorial specificity of each sample was observed according to the incorporation of the flavors. As for the nutritional composition of the beverage, it is observed that it presents 3.22% of lipids, 0.22% of ashes, 2.07% of proteins, 4.79% of carbohydrates and energy value of 56.46 Kcal. Close values were obtained after addition of flavor. From the evaluation of the bioacessible compounds content of the minerals calcium and phosphorus, it was verified that these were presented in low values for the evaluated formulations.